CULTURE AS A FOUNDATION FOR LEARNING STRATEGY INNOVATION: A CASE STUDY FROM IHOSY, MADAGASCAR - Claudette, Andriantenaina; Ravaoarisoa Simonette Augustin; Koto Bernard (JURNAL STRATEGI PEMBELAJARAN, 2025)
This study aims to examine how local culture serves as a foundation for learning strategy innovation in Ihosy, Madagascar, where schools operate within strong communal traditions and limited educational resources. Using a qualitative case study approach, the research was conducted in three public secondary schools and one community learning center, selected for their active engagement with local cultural practices. A total of 24 participants, including school principals, teachers, students, parents or community elders, and education officers, were purposively and snowball-selected to capture diverse perspectives on teaching, learning, and cultural integration. Data were collected over two months through semi-structured interviews, non-participant classroom observations, and document analysis, allowing for triangulation and a comprehensive understanding of culturally grounded instructional practices. Thematic analysis of transcribed interviews and observation notes revealed that teachers act as cultural mediators, adapting curricula to integrate local traditions, storytelling, and communal problem-solving approaches, which enhance student engagement, comprehension, and collaboration. Community involvement was found to reinforce these strategies by providing authentic knowledge and fostering shared responsibility for learning. The findings also highlight the role of culturally relevant pedagogy in motivating students, improving classroom participation, and sustaining innovative instructional practices. The study concludes that culture is not a barrier but a critical resource for educational innovation in rural contexts, and it recommends professional development for teachers, structured mechanisms for community participation, and further research into the long-term impacts of culturally grounded learning strategies. These insights contribute to understanding how culture can be systematically leveraged to improve education in culturally diverse and resource-limited settings.